On-farm integration of forage legumes into cereal cropping systems in the Ethiopian highlands - Lupwayi, N.Z.; Tedla, A.; Regassa, H. (1996)
An on-farm trial, in which a wheat-clover mixed cropping treatment was compared with un-fertilised (control) and N-fertilised (23 kg N ha (-1)) pure wheat treatments, was conducted at Ginchi (2200 metres above sea level (m asl)) and Deneba (2600 m asl) in the Ethiopian highlands. Compared with the pure wheat control, inclusion of clover in the wheat at Deneba produced significantly more fodder dry matter (DM) (5.20 vs 3.16 t ha (-1)), with higher N yield (36.35 vs 12.68 kg N ha (-1)) and in vitro DM digestibility (48.6 vs 34.9 percent) was produced under mixed cropping, but this occured at the expense of wheat grain yield (0.91) vs 1.39 t ha (-1)). The N-fertilised wheat produced the highest grain yield at each site. Clover DM, nodule number, nodule size, nodule activity (internal colour) and nitrogen yield were all higher at Ginchi than at Deneba. In the second season, no residual effect of clover on wheat yield was detected. However, on the basis of the increase in feed quantity and quality, with little effect on wheat grain yield in the first season, it can be concluded that integration of wheat and clover production has potential to increase fodder availability for dry season feeding of livestock in the Ethiopian highlands.